2009
DOI: 10.1002/jobm.200800239
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of chromium(VI) contaminated soil by Streptomyces sp. MC1

Abstract: This work provides quantitative information on Cr(VI) reduction in soil samples by an indigenous actinomycete. Streptomyces sp. MC1, previously isolated from sugarcane, has shown ability to reduce Cr(VI) in liquid minimal medium. A reduction of 100 and 75% was obtained at initial Cr(VI) concentrations of 5 and 50 mg l(-1), respectively, after 48 h of incubation. Bioremediation ability of Streptomyces sp. MC1 was assayed in soil extracts and soil samples. Relative growth of Streptomyces sp. MC1 was 77 and 38% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 37 publications
2
53
1
Order By: Relevance
“…Cr(VI) reduction in minimal medium is much more time-consuming than in complex medium. Polti et al (2009Polti et al ( , 2010 Streptomyces sp. MC1 to reduce Cr(VI) to Cr(III) under different culture conditions: Cr(VI) reduction reached 45% after 3 days in minimal medium with glucose as carbon source.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cr(VI) reduction in minimal medium is much more time-consuming than in complex medium. Polti et al (2009Polti et al ( , 2010 Streptomyces sp. MC1 to reduce Cr(VI) to Cr(III) under different culture conditions: Cr(VI) reduction reached 45% after 3 days in minimal medium with glucose as carbon source.…”
Section: Discussionmentioning
confidence: 99%
“…MC1, a sugar cane isolated (Polti et al 2007). This strain in particular was able to reduce Cr(VI) in liquid minimal medium, soil extract, and soil samples, demonstrating its potential use in bioremediation processes (Polti et al 2009). Also, they characterized the chromate reductase enzyme from this strain.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[13] and Arthrobacter sp. [14] and actinomycetes [15]. The response of microorganisms towards toxic heavy metals is of importance in view of their interest in the reclamation of polluted sites.…”
Section: Introductionmentioning
confidence: 99%
“…Amoroso et al (2001), reported on Cr(VI) bioaccumulation by Streptomyces strains, whereas Laxman and More (2002) determined Cr(VI) reduction by Streptomyces griseus. Polti et al (2009), determined Cr(VI) reduction by Streptomyces sp. MC1 and later on characterize its chromate reductase activity (Polti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%